Tornar-se alfabetizadora - Valiengo, Amanda (Editora Oficina Universitária, 2021)
The discussion about literacy and training of Luso-Brazilian literacy teachers guides the debates in this book. By taking a close look at the realities of Continuing Education programs and their impacts on literacy processes, this study offers arguments and portraits that are born from the narratives of the main actors of these praxis: the literacy teachers. The background of this work is the history of teacher training, its methods of preparation, reflections and intersections that marked teacher training in these two countries. All this narrated by those who experienced, in practice, two of the government initiatives aimed at this end: the Letra e Vida Program (São Paulo/Brazil) and the National Program for Teaching Portuguese (Portugal). From the situations of welcoming and listening to the narratives of the study participants, the book proposes a mature discussion about the projection and real effectiveness of these teacher training programs, whose objective refers to the “humanization” of these educators, through instrumentalization theoretical and methodological. In these processes, the challenge posed is the creation of favorable conditions for studies and reflections on the role of school education, highlighting the teaching activity and that of the younger generations.